SPIRITUALITY OF MODERN YOUTH: MORAL VALUES AND THE PATH TO SPIRITUAL MATURITY (Scientific journal of the Fergana State University, 2026)
This article examines the spirituality of modern youth, their moral values, and ways to achieve spiritual maturity. It analyzes the role of moral values in the personal and social development of young people, as well as issues of spiritual education and social responsibility. Additionally, the article discusses methods for maintaining the spiritual stability of youth in the context of globalization and digital technologies.